2006
DOI: 10.1530/eje.1.02163
|View full text |Cite
|
Sign up to set email alerts
|

GH deficiency in patients irradiated for acromegaly: significance of GH stimulatory tests in relation to the 24 h GH secretion

Abstract: Background: Radiotherapy for pituitary adenomas frequently leads to GH deficiency (GHD). The characteristics of GH secretion in GHD induced by postoperative radiotherapy for acromegaly are not known. Hypothesis: In the long term, stimulated and spontaneous GH release is not different between patients with GHD treated by postoperative radiotherapy for acromegaly or for other pituitary adenomas. Design/subjects: We compared the characteristics of basal and stimulated GH secretion in patients with GHD, who had pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Little is known about the effects of GH replacement therapy in those who develop GHD after cure of acromegaly and reported data have been contradictory (5,20,22,23). van der Klaauw et al (23) recently concluded that the beneficial effects of GH replacement in patients with GHD during treatment of acromegaly are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the effects of GH replacement therapy in those who develop GHD after cure of acromegaly and reported data have been contradictory (5,20,22,23). van der Klaauw et al (23) recently concluded that the beneficial effects of GH replacement in patients with GHD during treatment of acromegaly are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The result is that less attention is given to possible postoperative GH deficiency (GHD). Indeed, there have been few reports on GHD after radiotherapy for acromegaly (3)(4)(5)(6) and there have only been few and contradictory studies conducted on small numbers of patients of GHD after TSS alone (7)(8)(9)(10). Therefore, a large number of patients undergoing surgery who were later deemed cured by the recent stringent criteria for cure of acromegaly were studied to determine the characteristics of GH-deficient patients with prior acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…As the cure criteria for acromegaly have become stricter, the space between cure on one side and GH deficiency (37,38) on the other has become narrow. Although subgroup analysis of the data presented by Holdaway et al (39) show that the presence of hypopituitarism in acromegaly patients does not have any significant influence on survival, increased mortality has been associated with hypopituitarism in general (40).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Treatment of acromegaly, however, can result in GHD in some patients, especially after previous radiotherapy (5). Several parameters of cardiac morphology and function were altered in our patients with GHD after acromegaly.…”
Section: Discussionmentioning
confidence: 58%
“…However, surgical treatment of GH excess followed by radiotherapy can result in GH deficiency (GHD) (5) and GHD per se is also associated with cardiomyopathy. Cardiac manifestations of GHD include a decrease in LV mass and LV ejection fraction (LVEF) (6)(7)(8)(9)(10)(11)(12), which is correlated to the severity of GHD (8).…”
Section: Introductionmentioning
confidence: 99%